Globalization and the transformation of the national political space: Six european countries compared - Hanspeter Kriesi; Edgar Grande; Romain Lachat; Martin Dolezal; Simon Bornschier; Timotheo Frey (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2005)
In this paper, we present the basic ideas, the design and some key results of an ongoing research project on the transformation of the national political space in Western Europe. We start from the assumption that the current process of globalization or denationaliza-tion leads to the formation of a new structural conflict in Western European countries, opposing those who benefit from this process to those who tend to loose in the course of the events. The structural opposition between globalization "winners" and "losers" is expected to constitute potentials for the political mobilization within national political contexts. The political mobilization of these potentials, in turn, is expected to give rise to two intimately related dynamics: the transformation of the basic structure of the na-tional political space and the strategic repositioning of the political parties within the transforming space. We present several hypotheses with regard to these two dynamics and test them empirically on the basis of newly collected data concerning the supply side of electoral politics from six Western European countries (Austria, Britain, France, Germany, the Netherlands and Switzerland). The results indicate that in all the countries, the new cleavage has been embedded into the existing two-dimensional national political spaces. In the process, the meaning of the original dimensions has been transformed. The configuration of the main parties has become triangular even in a country like France where it used to be bipolar.
Keywords: 320; Sozialer Konflikt; Globalisierung; Politik; Nationalstaat; Interessenpolitik; Vergleich; Österreich; Großbritannien; Frankreich; Niederlande; Schweiz; Deutschland